Penerapan Metode Machine Learning Dalam Memprediksi Keberhasilan Panggilan Telemarketing Menjual Produk Bank - Ahmad Fauzi; Fanny Fatma Wati; Indah Sulistyowati; Muhammad Faittullah Akbar; Eka Rahmawati; Ratna Kurnia Sari (Indonesian Journal on Software Engineering (IJSE), 2020)
Abstract: Competition between banks can be seen from the various attempts by banks to find customers through various marketing activities in order to get as many customers as possible. In the past, business actors offered goods or services to consumers in a face-to-face manner, now by utilizing existing and sophisticated technology, they can use long-distance communication tools such as telephone and fax, as well as other electronic media. To make it easier to manage customer data, a data calcification is needed. Machine Learning Algorithms can be used to predict or classify data. One of the algorithms in Machine Learning is the Naive Bayes method. Naive Bayes is a simple probabilistic classification that calculates a set of probabilities by summing the frequency and value combinations from a given dataset. This research will predict a successful Telemarketing call in selling Bank products to customers. The Naive Bayes algorithm and the Backward Elimination feature selection can increase the accuracy value in predicting the success of telemarketing in selling bank products well, as evidenced by the accuracy value generated by Naive Bayes of 83.04%, then after being applied with the selection of the backward elimination feature it increases by 6.41. % to 89.45%. Keywords: Telemarketing, Machine Learning, Naive Bayes Abstrak: Persaingan antar bank dapat dilihat dari berbagai upaya bank dalam mencari nasabah dengan berbagai kegiatan pemasaran agar mendapat nasabah sebanyak-banyaknya. Dahulu para pelaku usaha menawarkan barang atau jasa kepada konsumen dengan cara bertatap muka langsung, sekarang dengan memanfaatkan teknologi yang ada dan canggih bisa menggunakan alat komunikasi jarak jauh seperti telepon dan fax, serta media elektronik lainnya. Untuk mempermudah mengelola data nasabah maka dibutuhkan sebuah pengkalsifikasian data. Algoritma Machine Learning dapat digunakan dalam memprediksi atau mengklasifikasikan sebuah data. Salah satu algoritma dalam Machine Learning adalah metode Naive Bayes. Naive Bayes merupakan sebuah pengklasifikasian probabilistik sederhana yang menghitung sekumpulan probabilitas dengan menjumlahkan frekuensi dan kombinasi nilai dari dataset yang diberikan. Pada penelitian ini akan memprediksi sebuah keberhasilan panggilan Telemarketing dalam menjula produk Bank kepada para nasabah. Algoritma Naive Bayes dan seleksi fitur Backward Elimination mampu meningkatkan nilai akurasi dalam memprediksi keberhasilan telemarketing dalam menjual produk bank dengan baik, dibuktikan dengan nilai akurasi yang dihasilkan naive bayes sebesar 83,04 %, kemudian setelah diterapkan dengan seleksi fitur backward elimination meningkat sebesa 6,41% menjadi 89,45%. Kata kunci: Telemarketing, Machine Learning, Naive Bayes